Corporate Venture Capital, Disembodied Experimentation and Capability Development - KEIL, Thomas (Institutional Knowledge at Singapore Management University, 2008)
Studies invoking a capabilities lens often ascribe deliberateness in organizational decisions to develop new capabilities. Drawing on five longitudinal case studies of large, global firms in the information and communication technology sector, we examine how firms engender cognizance of their future capability needs in situations characterized by high decision-making uncertainty. We develop a theoretical account of how firms use investments in start-ups to actively engage in experimentation outside organizational boundaries, a learning process which we term as disembodied experimentation. Disembodied experimentation creates awareness of voids in the capability base of an incumbent and helps to overcome inertial restraints thereby influencing the decision to invest in capability development. The relationship between learning from disembodied experimentation and the decision to develop capabilities is moderated by knowledge brokering functions and adaptation complexity.